PENGARUH PELATIHAN, KOMPETENSI SYARIAH DAN STRES KERJA TERHADAP KINERJA KARYAWAN BANK RAKYAT INDONESIA SYARIAH KANTOR CABANG SIDOARJO - Agustina, Nia Tri; Cahyono, Hendry (Universitas Negeri Surabaya, 2020)
AbstractThe majority of the educational background of human resources in sharia banking is general education that is trained in a short time sharia financial knowledge, other than that, the stress level is also becoming an issue of sharia banking employees that have an impact on their performance. This study aims to determine the effect of training variables, sharia competence and work stress on the performance of employees of Bank Rakyat Indonesia Syariah Sidoarjo Branch Office. The research used quantitative method with an associative approach. Using primary data sources through questionnaires with a Likert scale that distributed to the respondents. Data analysis using the PLS (Partial Least Square) method by evaluating the outer and inner model. The results showed that partially Sharia training and competence had a positive impact on employee's performance, while work stress had a negative impact to them.Keywords: training, sharia competence, work stress, performance